Evolution of metamorphic processes in the Neoarchean mafic granulites of the Qingyuan Terrane in northern Liaoning, North China Craton - CUI Runze; WEI Chunjing (Dizhi lixue xuebao, 2023)
Multiple interpretations exist regarding the tectonic evolution model of the Neoarchean North China Craton, requiring a more in-depth study of metamorphic processes. Systematic petrographic observations, mineral chemical analysis, phase equilibrium modeling, and zircon dating were conducted on the basic granulites from Qingyuan in northern Liaoning to elucidate their metamorphic evolution processes and geological significance. The selected samples of mafic granulites were divided into the garnet-bearing domain (19DJ07-GD) and garnet-free domain (19DJ07-NGD), with the garnet-bearing region displaying a banded and inhomogeneous distribution. Both domains exhibit two generations of granulite facies assemblages. In the garnet-bearing domain, the first-generation metamorphic mineral assemblage includes garnet + clinopyroxene + orthopyroxene + hornblende + biotite + plagioclase + quartz. Notably, the first-generation plagioclase (Pl1) exhibits a complex compositional zoning, with anorthite content (xAn) increasing from the core to the mantle and then decreasing towards the rim. Similarly, the titanium component zoning in the first-generation amphibole (Amp1) follows a pattern of increasing from the core to the mantle and then decreasing towards the rim. Based on mineral assemblages and corresponding component zoning, it is inferred that the first-generation granulite facies metamorphic process followed a counterclockwise P-Tpath, involving a pre-peak P-T rise stage and a post-peak P-T drop stage. Phase equilibrium modeling constrains the peak conditions at 0.8~0.9 GPa/900~950 ℃, indicative of high-ultrahigh-temperature (HT-UHT) metamorphism conditions. Zircon dating results yielded a post-peak cooling age of 2498±6.9 Ma (MSWD=0.39). Considering the regional "dome-and-keel" tectonics, the counterclockwise P-T path, and the metamorphic timing of supracrustal rock nearly synchronous with late-stage TTG magmatic pulses, the UHT metamorphism of the supracrustal rocks is believed to be controlled by the unique Archean vertical tectonics/sagduction system. The second-generation metamorphic assemblage is characterized by locally formed coronas or symplectites of garnet + quartz ± clinopyroxene, representing high-pressure (HP) granulite facies metamorphism associated with a Paleoproterozoic orogenic event.